Respuesta :

Answer: No Solution

Step-by-step explanation:

Given

2(6x+5)=-3(-4x+3)

Expand parenthesis

2·6x+2·5=(-3)·(-4x)+(-3)·3

12x+10=12x-9

Subtract 12x on both sides

12x+10-12x=12x-9-12x

10=-9

10 will never equal -9, which means this is No Solution

Hope this helps!! :)

Please let me know if you have any questions

Answer:

no solutions

Step-by-step explanation:

+ * - = -

- * + = -

- * - = +

+ * + = +

2 (6X + 5) = -3 (-4X+3)

- distribute

12X + 10 = 12X - 9

       -10            -10

12X = 12X - 19

- 12X   - 12 X

0 ≠ - 19

or you can skip all of that and just realize that there cannot be the 12X on both sides but the second term is different